Mewujudkan Kebijakan Pertanian yang Pro-Petani - Suseno, Djoko; Suyatna, Hempri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2007)
As an agrarian country, Indonesia needs to develop its agricultural products. Related to this, the Indonesian farmers have signifcant roles on the development of agriculture in Indonesia. Nonetheless, previous agricultural policies have failed to obtain the goals. Another consequence befell to the farmers that have been marginalized. To respond the problems, a new agricultural policy needs to be created. This article show important considerations to establish the new pro-farmer agricultural policy in Indonesia